2009
DOI: 10.1159/000214214
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Activity of SGLT2 in Diabetes Induced by Streptozotocin: Relationship with the Lipid Environment

Abstract: Background/Aims: Diabetes mellitus may impact on the regulation of renal Na+-glucose cotransporter type 2 (SGLT2), however, previous studies have yielded conflicting results on the effects of streptozotocin (STZ)-induced diabetes on SGLT-mediated glucose transport. Methods: Diabetes was induced in male Wistar rats. The studies were performed at 3 (D3), 7 (D7) and 14 (D14) days after a single i.p. injection of STZ. SGLT2 activity was measured using α-14C-methyl glucose uptake in brush-bord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 69 publications
2
17
0
1
Order By: Relevance
“…Other studies found unchanged renal SGLT1 protein expression [114-116] or reduced renal expression and activity of SGLT1 [117] in diabetic rodent models. Using Sglt1 −/− mice as a critical negative control for the antibody, renal membrane protein expression of SGLT1 was found to be reduced in Akita mice, a genetic model of T1DM [107].…”
Section: Diabetes Increases Renal Sglt1-mediated Glucose Reabsorptionmentioning
confidence: 99%
“…Other studies found unchanged renal SGLT1 protein expression [114-116] or reduced renal expression and activity of SGLT1 [117] in diabetic rodent models. Using Sglt1 −/− mice as a critical negative control for the antibody, renal membrane protein expression of SGLT1 was found to be reduced in Akita mice, a genetic model of T1DM [107].…”
Section: Diabetes Increases Renal Sglt1-mediated Glucose Reabsorptionmentioning
confidence: 99%
“…Diabetes may not uniformly increase renal expression of SGLTs because some studies found unchanged or even reduced renal SGLT expression and/or activity in diabetic rodent models (19, 56, 57). Studies in primary cultures of renal proximal tubule cells indicated that high-glucose-induced oxidative stress can reduce SGLT expression and activity (Figure 3) (58).…”
Section: Glucose Transport In the Diabetic Proximal Tubulementioning
confidence: 99%
“…Снижение экспрессии SGLT2 в почках зафиксировано при стрептозотоциновом СД (модель СД1) у мышей линии C57BL/6 [11] и у крыс линии Wistar [14]. В другом исследовании зафиксировано повышение экспрессии SGLT2 как на фоне высокосолевой диеты, так и на фоне диеты с нормальным содержанием натрия в данной модели СД [15].…”
Section: роль Sglt2 в почечной реабсорбции глюкозы в норме и при сдunclassified